Tofu Liquid Waste Treatment Process Using Anaerobic Baffled Reactor with Cow Stool and Lactobacillus casei Addition - Febriningrum, Panca Nugrahini; Astawa, I Nyoman Endra (Indonesian Journal of Chemical Science, 2022)
Tofu liquid waste causes ecosystem damage due to its high organic matter content. Anaerobic baffled reactor (ABR) is a waste treatment in the absence of oxygen where there is a sedimentation process using activated sludge. This process converts organic material into methane gas, ammonia and hydrogen sulfide. This study aims to determine the effect of addition of cow feces and Lactobacillus casei bacteria on decreasing levels of COD, TSS, VSS, pH and gas pressure. The research process was carried out in two stages of processing tofu liquid waste, namely the batch and continuous stages. Batch and continuous processes use an ABR reactor which has four chambers. Parameters measured include, COD, TSS, VSS, pH and Gas Pressure. The results obtained by the best batch process were obtained without the addition of bacteria, the ratio of cow feces and activated sludge was 1:4, the COD removal was 81.63%, the TSS removal was 1,300 mg/L, the VSS removal was 1,200 mg/L and the pH value final 8.0 for 6 days. The best processing time in the continuous process is 6 hours, the COD removal is 78.12%, the TSS removal is 600 mg/L, the VSS removal is 500 mg/L and the final pH value is 6.5. It can be concluded that the more cow feces added, the faster and greater the removal of COD, TSS, VSS and pH values ​​tended to increase in the treatment of adding bacteria.